Multiple Immune Features-Based Signature for Predicting Recurrence and Survival of Inoperable LA-NSCLC Patients - Guo, Meiying; Li, Wanlong; Li, Butuo; Zou, Bing; Wang, Shijiang; Fan, Bingjie; Sun, Xindong; Wang, Linlin (Frontiers in Oncology, 2020)
Introduction: The immune status of tumor microenvironment is extremely complex. One single immune feature cannot reflect the integral immune status and its prognostic value was limited. We postulated that the immune signature based on multiple immuno-features could markedly improve the prediction of post-chemoradiotherapeutic survival in inoperable locally advanced non-small-cell lung cancer (LA-NSCLC) patients. Methods: In this study, 100 patients who were diagnosed as inoperable LA-NSCLC between January 2005 and January 2016 were analyzed. A 5-immune feature-based signature was then constructed using the nested repeat 10-fold cross validation with least absolute shrinkage and selection operator (LASSO) Cox regression model. Nomograms were then established for predicting prognosis. Results: Immune signature combining 5 immuno-features were significantly associated with overall survival (OS) and progression-free survival (PFS, P = 0.002 and P=0.014, respectively) in patients with inoperable LA-NSCLC; and at a cutoff of -0.05 stratified patients into two groups with 5-year OS rates of 39.8% and 8.8%, and 2-year PFS rates of 22.2% and 5.5% for the high- and low-immune signature groups, respectively. Integrating immune signature, we proposed predictive nomograms, which were better than the traditional TNM staging system in terms of discriminating ability (OS: 0.692 vs. 0.588; PFS: 0.672 vs. 0.586, respectively) or net weight classification (OS: 32.96%; PFS: 9.22%), suggesting that immune signature plays a significant role in improving the prognostic value. Conclusion: Multiple immune features based immune signature could effectively predict recurrence and survival of inoperable LA-NSCLC patients, and complemented the prognostic value of the TNM staging system.